Large-Scale Survey for Tickborne Bacteria, Khammouan Province, Laos - Andrew J. Taylor; Khamsing Vongphayloth; Malavanh Vongsouvath; Marc Grandadam; Paul T. Brey; Paul N. Newton; Ian W. Sutherland; Sabine Dittrich (Emerging Infectious Diseases, 2016)
We screened 768 tick pools containing 6,962 ticks from Khammouan Province, Laos, by using quantitative real-time PCR and identified Rickettsia spp., Ehrlichia spp., and Borrelia spp. Sequencing of Rickettsia spp.–positive and Borrelia spp.–positive pools provided evidence for distinct genotypes. Our results identified bacteria with human disease potential in ticks in Laos.